Pengaruh Pemberian Akupresur terhadap Nyeri Persalinan Fase Aktif - Aris Prastyoningsih; Siti Wahyuni; Christin Bumi Pangesti; Dwi Margareta Andini (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Contraction pain is main problem for patients in the 1st stage of labor in active phase. Labor pain in first stage of the active phase can be treated with acupressure at points L14 and SP6. The L14 and SP6 acupressure points can stimulate release of hormone oxytocin from pituitary, which will stimulate uterine contractions, thereby helping the labor process to be better and reducing pain during labor. The aim of this study was to determine how acupressure impacts labor pain during active phase of the first stage. Design of this research is one group pre-post test. This study involved 30 women giving birth normally, in 1st stage of the active phase, who had no abnormalities or injuries at L14 and SP6 locations. Ttool used is Wong Baker Pain Scale. The results showed that maternal patients in 1st active phase had an average pain scale of 8.03 before being given acupressure, and pain scale dropped to 3.26 after being given acupressure. There was a significant difference between the groups before and after acupressure with a p value of 0.000. There is an effect of giving acupressure on the intensity of pain in mothers giving birth during the first active phase